Effect of Oligohydramnios on Fetal Heart Rate Patterns during Term Labor Induction - Rhoades, Janine S.; Stout, Molly J.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2019)
Objective To estimate the effect of oligohydramnios on fetal heart rate (FHR) patterns in patients undergoing induction of labor (IOL) at term.Study Design Secondary analysis of a prospective cohort study of consecutive term, singleton deliveries from 2010 to 2015. We included all patients who underwent IOL. Our primary outcomes were electronic fetal monitoring (EFM) characteristics in the 2 hours preceding delivery. Outcomes were compared between those induced with oligohydramnios and those induced without a diagnosis of oligohydramnios. Our secondary outcome was composite neonatal morbidity. Logistic regression was used to control for confounders.Results Of 3,787 patients who underwent IOL, 147 had a diagnosis of oligohydramnios and 3,640 were included in the no oligohydramnios group. There was no significant difference in EFM characteristics between the two groups. There was no difference in composite neonatal morbidity. In patients with oligohydramnios, EFM patterns with baseline tachycardia for 30 minutes or greater were significantly associated with composite neonatal morbidity (31.3 vs. 5.3% adjusted odds ratio 8.63, 95% confidence interval 2.18, 34.1]).Conclusion Term patients undergoing IOL with oligohydramnios had EFM patterns that did not differ from their induced peers.
Keywords: electronic fetal monitoring; fetal heart rate; induction of labor; oligohydramnios